Digitalization of the Ukrainian economy during a state of war is a necessity of the time - Verbivska, Liudmyla (Amazonia Investiga, 2023)
This article explores the digital economy's importance for Ukraine's development, analyzing its current state, identifying digitization opportunities and threats, and assessing readiness for adopting digital technologies. The study employs a range of methods to assess the extent of development of Ukraine's digital economy. It examines global trends in digital transformation and evaluates Ukraine's digital resources and information infrastructure. The advantages and disadvantages of implementing digital technologies in the Ukrainian economy are identified. The study reveals that Ukraine lacks sufficient digital resources compared to other European countries. However, it highlights the country's active efforts in developing its information infrastructure and emphasizes the importance of digitization for economic growth. The research identifies the main prerequisites for the global era of the digital economy and establishes the significance of information and communication technologies for economic development and people's well-being. Conclusion: Based on the analysis of Ukraine's digital economy, the study concludes that digitization should be a priority direction for the country. It proposes key measures for effectively utilizing innovative technologies and stimulating the development of the Ukrainian digital economy in the "digital era." Expediting the advancement of the Ukrainian economy in the realm of innovative technologies is considered essential for its future progress and well-being.
Verbivska, L., Abramova, M., Gudz, M., Lyfar, V., & Khіlukhа О. (2023). Digitalization of the Ukrainian economy during a state of war is a necessity of the time. Amazonia Investiga, 12(68), 184-194.
Keywords: digitalization, digital economy, European integration process, digital technologies, digital transformation.